Memudarnya nilai-nilai gotong royong pada era globalisasi - Al Fikri, Moh Fatih (Maliki Interdisciplinary Journal, 2025)
Mutual cooperation (gotong royong) is a social tradition that has been embedded in Indonesian culture since ancient times. This value is reflected in the nation’s ideological foundation, Pancasila, particularly the third principle, which emphasizes Indonesian unity. The practice of mutual cooperation serves not only as a means to lighten workloads through togetherness, but also as an instrument for creating a harmonious and cooperative social climate in resolving shared problems. The spirit of mutual cooperation is a distinctive Indonesian identity that distinguishes it from other nations. However, the currents of globalization have had a significant impact on the continuity of this tradition. Modernization and the penetration of Western culture have caused a shift in values, resulting in a fading spirit of solidarity and community togetherness. This phenomenon underscores the challenge of preserving the nation’s noble values ​​amidst the dynamics of globalization.